Efektifitas PERGUB Pembentukan BKSP Provindi Kepri Dalam Menjawab Tantangan MEA 2015 - Rina Shahriyani Shahrullah; Lu Sudirman; Lusi Nila Sari (Journal of Judicial Review, 2014)
The deal of ASEAN Economic Community 2015 implementation in labour areas that is marked conservatively skill labouring flow. Concerning with Indonesian labouring interest, at Kepulauan Riau Province being formed by Coordination Board Profession of certification (BKSP) through Governor regulation Number 2 Years 2007 on the fifteenth 02 Marches 2007. Severally constraint which can be inventoriesed performing, for example: Organisational institute, Finance budget, and Organisational management. In order to BKSP'S organization wheels can walk to accord expectation, therefore has to get settles about problem bound up , and has to twine various institute or organization to be asked out collaboration and builds network.